The Integration of Turats and Digital Technology in Islamic Religious Education: Developing a Learning Model to Strengthen Students' Islamic Critical Reasoning - Muhammad Syarwani (Universitas Islam Sultan Agung, 2026)
This study aims to develop and test the effectiveness of the Turats-Digital Integration Model for Strengthening Islamic Critical Reasoning (ITD-NKK), an Islamic Religious Education (PAI) learning model that combines classical turats studies with the use of digital technology to address the need for strengthening students' Islamic critical reasoning amid the rapid flow of digital religious information whose validity is not always accountable. The study employs a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate) combined with a quasi-experimental non-equivalent control group design. Trial subjects were students from two parallel classes at the secondary education level, serving as the experimental and control groups respectively. Data collection instruments included expert validation sheets, student and teacher response questionnaires, Islamic critical reasoning tests (pre-test and post-test), and learning implementation observation guidelines. Quantitative data were analyzed using an independent sample t-test and N-Gain calculation, while qualitative data were analyzed descriptively and interpretively. The findings indicate that the ITD-NKK model is valid, practical, and effective for implementation, with a significant increase in Islamic critical reasoning among experimental group students compared to the control group. The model offers a learning flow that combines turats text reading with digital verification activities, structured online forum discussions, and contextual analysis assignments supported by digital applications. The implications of this study affirm that integrating turats and digital technology can be an effective strategy to equip students with Islamic critical thinking skills grounded in authoritative sources, rather than mere passive consumption of digital religious information.